Introduction - Gioia, Gina (Revista Ítalo-española de Derecho procesal, 2025)
The pursuit of effective justice for small claims disputes, both at national and cross-border levels, remains a cornerstone of legal and procedural reforms across Europe. Over the past two decades, the European legal landscape has witnessed substantial efforts to streamline and harmonize small claims procedures, aiming to balance efficiency, accessibility, and fairness. From the introduction of specialized procedural tools like the European Small Claims Procedure (ESCP) to innovative technological solutions such as blockchain and AI-driven automation, the collective endeavor reflects a growing recognition of the need to adapt justice systems to contemporary societal demands...